Epik Platform - Design and Development of Interactive Puzzles as an Educational Activity - Catela, André Simão Pereira (2020)
Nowadays, many types of games are used as an educational tool, capturing more easily students attention by keeping them interested in the lectured topics, which accelerates the learning process and provides collaborative learning in an entertaining way. Puzzle games in specific are one of the most used games for educational purposes due to its variety of formats, themes, and logics to solve them, having an adjustable difficulty according to students capacity of problem solving, with the view of developing these capacities. Despite this gain of popularity, there are not a lot of options regarding computacional platforms to develop educational games. The Epik Platform consists in a web-based framework dedicated to the management of didactic contents and development of educational games. With this platform, the creation and edition of games turned to the educational environment is quite simplified, which makes it a good option for this purpose [1]. However, this platform’s games only include quiz type activities of multiple choices, true or false and matching, not offering much variety for the users to work with. Having this in mind, the development of interactive puzzle activities of different types, which is the main objective of this thesis, will allow the extension of the range of activities available in the set of games at the Epik platform. To be able to develop the interactive puzzle activities, a study must be done so that the right framework is selected according to the needs and limitations of development. With the addition of this new type of activity, the users will be able to develop their own interactive puzzles according to the three different puzzle games included, each one having a specific development environment for it. Overall, the platform will now be able to provide games performing a group of activities of different kinds in the same game, making it more appealing for the users. At a global level, this dissertation is inserted on the project ’Restructure, Flexibilize and Update the Epik Platform’, which aims to reimplement, extend and restructure features of the Epik platform, whose development was made for a previous master thesis by a student (Bruno Sampaio) [2].